2002
DOI: 10.1359/jbmr.2002.17.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Smad1 Transcriptional Activity by Ras-Extracellular Signal-Regulated Kinase Pathway: A Possible Mechanism for Collagen-Dependent Osteoblastic Differentiation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 41 publications
(59 reference statements)
4
77
1
4
Order By: Relevance
“…These characteristics facilitate the ingrowth and remodeling of new bone in vivo. The cooperation between BMP-2, collagen, and noncollagenous proteins plays an important role in the differentiation of BMSCs to osteoblasts and osteoinduction in vivo (Globus et al 1995, Schneider et al 2001, Suzawa et al 2002, Xiao et al 2002. In this study, we found that self-secreted ECM served as a good carrier for BMSCs in the repair of segmental tibial bone defects in goats, although selfsecreted ECM has little osteoconductivity.…”
Section: Discussionmentioning
confidence: 49%
“…These characteristics facilitate the ingrowth and remodeling of new bone in vivo. The cooperation between BMP-2, collagen, and noncollagenous proteins plays an important role in the differentiation of BMSCs to osteoblasts and osteoinduction in vivo (Globus et al 1995, Schneider et al 2001, Suzawa et al 2002, Xiao et al 2002. In this study, we found that self-secreted ECM served as a good carrier for BMSCs in the repair of segmental tibial bone defects in goats, although selfsecreted ECM has little osteoconductivity.…”
Section: Discussionmentioning
confidence: 49%
“…On the other hand, stimulation of mouse MSC and murine preosteoblasts MC3T3-E1 cells with BMP-2 also promoted both ERK expression and ERK activity 12) . Reducing ERK activity decreased ALP activity, suggesting that BMP-2 induced ERK activation and that this ERK activation is required for ALP activation 29,30) . These contradictory reports indicated that the effects of BMP-2 on osteogenic differentiation are regulated by MAPK signaling pathways but that their mechanism of regulation is very complicated and is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin activation of focal adhesion kinase (FAK) induces Ras and the downstream Erk in ostoeblasts. FAK activated Ras-Erk stimulates Smad-1 activity in response to BMP-2 in osteoblasts (Suzawa et al, 2002). The Ras-Erk-signaling pathway is activated by serum.…”
Section: Discussionmentioning
confidence: 99%